Effects of effective ERP system utilization on enterprise economic sustainability through product life cycle cost control - Zaid Jaradat; Ahmad AL-Hawamleh; Marwan Altarawneh; Saqer Al-Tahat; Muhannad Akram Nazzal (Journal of Business and Socio-Economic Development)
Purpose – The purpose of this study is to investigate the effects of effective enterprise resource planning (ERP) system utilization on enterprise economic sustainability through product life cycle cost control. Design/methodology/approach – Data were collected from key stakeholders in Jordanian industrial firms. These stakeholders included company managers, production managers, accounting heads and cost accounting staff. A comprehensive questionnaire was developed to gather their insights, ensuring a thorough understanding of their perspectives on the relationship between ERP systems, cost management and sustainability. Findings – The study revealed that the effective use of ERP systems positively impacted the control of product life cycle costing, which in turn positively influenced the economic sustainability of enterprises in the Jordanian industrial sector. The study’s outcomes underscore the significance of investing in employee training to optimize the use of ERP systems and improve overall organizational performance. Practical implications – The study offers insights for managers and policymakers in the Jordanian industrial sector, highlighting the importance of effectively implementing and utilizing ERP systems to control product life cycle costs and enhance economic sustainability. Originality/value – This study contributes significantly to the existing literature by delving into the effects of effective ERP system utilization on enterprise economic sustainability through product life cycle cost control – an area that has not been extensively studied.